An assessment of fish production in Pathumthani province, Thailand - Monthip Sriratana; Edwards, Peter; Samorn Muttamara; Chongrak Polprasert; Royal Danish Government (Bangkok : Asian Institute of Technology, 1978)
This study dealt with the assessment of fishery production in Pathumthani Province in the Kingdom of Thailand. The study concentrated on this area because it is predominantly rural in character, it has an abundant year-round supply of water, and is close to the Bangkok metropolitan area where fish could be marketed. Specifically, the study dealt with assessment of subsistence level fishing in the area--the different fishing gears used and their methods and efficiencies, and the level of wild fish production. It appeared that a large number of people use primitive methods of catching wild fish resulting in low productivity. The study also assessed the state of development of fish farming on five types of fish--Tilapia nilotica, Pangasius pangasius , Pontius gonionotus, Cl arias macrocephalus and Ophicephalus striatus. A general finding is that aquaculture in the province is still primitive and much improvement has yet be done. To assess the sociological linkage of freshwater fishery in the province, fish consumption pattern was investigated. There appeared a great demand potential . Assessment of the capabilities of water bodies (Klongs and Chao Phya river) to hold large fish population was realized through measurement of plankton densities. A consider able variation of plankton densities existed with Chao Phya river having the lowest density. The whole study was done through survey questionnaires, actual interviews, actual laboratory sampling analysis for selected water bodies, and digging of relevant information from different government sources.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science of the Asian Institute of Technology, Bangkok, Thailand
Thesis (M. Sc.) - Asian Institute of Technology, 1978
Keywords: Fish-culture -- Thailand -- Pathum Thani